Aggregate hazard function in price-setting: A bayesian analysis using macro data - Fang Yao (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
This paper presents an approach to identify aggregate price reset hazards from the joint dynamic behavior of inflation and macroeconomic aggregates. The identification is possible due to the fact that inflation is composed of current and past reset prices and that the composition depends on the price reset hazard function. The derivation of the generalized NKPC links those compostion effects to the hazard function, so that only aggregate data is needed to extract information about the price reset hazard function. The empirical hazard function is generally increasing with the age of prices, but with spikes at the 1st and 4th quarters. The implication of this finding for sticky price modeling is that the pricing decision is characterized by both time- and state-dependent aspects.
Keywords: E12; E31; 330; Sticky prices; Aggregate hazard function; Bayesian estimation; Preisrigidität; Statistische Bestandsanalyse; New-Keynesian Phillips Curve; Dynamisches Gleichgewicht; Bayes-Statistik; Schätzung; USA